Not Alone Anymore! Sexual Harassment, Feminist Tsunami, and New Coalitions in Chilean Universities (Polis (Santiago), 2021)
During the last forty years there has been a fairly large body of research focused on sexual harassment in Global North universities.  At the same time, there is relatively little on sexual harassment in Latin American universities.  This article explores the Chilean case, where, from 2015 to the present, there have been an ever-increasing number of sexual harassment complaints at universities. As a result, in 2018 the Feminist Tsunami occurred, led by feminist students. In this article we will use press sources, interviews and discussions groups with students and feminist activists in order to analyze the Feminist Tsunami and sexual harassment at universities.  At the same time, we will also explore some of the resistances developed by feminist students, academics and professionals, inside and outside of universities, when thinking about anti-harassment strategies and coalitions.  Our hypothesis is that it was the emergence of diverse coalitions and networks, between feminist students, academics and professionals that allowed for the emergence of a very strong anti-harassment position at universities, as well as a powerful intergenerational feminist front to combat sexual harassment, a relatively invisible type of violence up until that moment.
Keywords: Sexual harassment; coalitions and networks; feminist movement; university; Chile.